Sistem Pendukung Keputusan Penentuan Film Berdasarkan Minat dengan Metode Weighted Product - Lemantara, Julianto (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Film production is increasing every time, making it difficult for people to decide which film to watch. Various film genres and film ratings often confuse people in choosing which film recommendations to watch based on each individual’s interests. Based on a survey that was conducted by distributing questionnaires to 72 respondents from film lovers, the survey results showed that 88.6% of people felt confused about what film to watch, 84% of people stated that the need to watch films increased during the pandemic. Therefore, this study aims to build a Decision Support System (DSS) for selecting films based on interest using the Weighted Product (WP) method. In this study, the criteria used in the WP method are year of release, genre, rating, production costs, and revenue. The study results showed that a DSS using the WP method can help people recommend films based on each individual's interests. The survey results showed that 98.4% of respondents feel helped by this DSS and 93.5% are interested in using this DSS to recommend film to watch.